Primera esofagectomía Ivor-Lewis con total mínima invasión y toracoscopía uniportal en Costa Rica. Reporte de caso. - Cubillo, Albert Bolaños (2023)
A 70-year-old healthy man was referred to our Thoracic Surgery Service at Dr. Rafael Angel Calderón Guardia Hospital (CCSS), with diagnosis of esophageal adenocarcinoma, Siewert 1, cT3N0M0. The patient underwent neo-adjuvant chemo-radiation therapy and four weeks after finished radiotherapy, our team performed an Ivor-Lewis totally minimal invasive esophagectomy with laparoscopic gastroplasty and right uniportal thoracoscopy with intrathoracic side-to-side semi mechanic esophago-gastric anastomosis. No post-operative complications were documented. The patient was discharged in post-operative day 8. Pathological study confirmed the diagnosis of adenocarcinoma ypT3N1M0 Stage IIIB. Four months later, there were no signs of local recurrence or stricture. This is the first Ivor-Lewis esophagectomy in Costa Rica with this uniportal thoracoscopic approach. This technique would help reduce post-operative pain, better cosmesis, with less risk of late stricture, faster recovery and less hospital stay.